Population and Level of Noctuidae Pest Attack on Sweet Corn (Zea Mays Saccharata Sturt.) - Agustin, Eva Tri; Rahmadhini, Noni; Kusuma, Ramadhani Mahendra (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Sweet corn (Zea mays saccharata Sturt) is a food plant from the family grass, and cultivating sweet corn is more profitable because it has high economic value on the market. The growth phase of sweet corn plants often experiences a decrease in production yields, even crop failure due to pest attacks. This research aims to determine the pest population and the level of Noctudiae pest attacks that attack sweet corn plants. The study was conducted on moorland in Pilanggot Hamlet, Wonokromo Village, Tikung District, Lamongan Regency, East Java, from May to July 2023. This research used a selected random sampling survey method, namely observations on five plots, and each plot contained 48 observed plants. Observations began when the sweet corn plants were 14 HST and carried out once a week, 10 observations with 7-day intervals, namely in the vegetative phase (14, 21, 28, 35, 42) and generative phase (49, 56, 63, 70 and 77 HST). ). The research results show that the highest population of Noctuidae pests is the armyworm (Spodoptera frugiperda), with as many as 63 individuals with a relative abundance of 54%. The Noctuidae pests found were the armyworm (Spodoptera frugiperda), moth (Spodoptera litura), and cob borer (Helicoverpa armigera). The highest attack percentage is 25%, but it is still mild.